2017
DOI: 10.1504/ijmr.2017.10003722
|View full text |Cite
|
Sign up to set email alerts
|

Energy Modelling for FDM 3D Printing from a Life Cycle Perspective

Abstract: Advances in 3D printing is penetrating in many industries. It is changing the way of doing manufacturing business and people's life. Performing energy and related environmental impact analysis of this technology is necessary and profound. In this paper, energy modelling is studied for FDM printing from a life cycle perspective. For a typical FDM life cycle, the stages covered are material production, printing, post-processing and related transportation. For each stage, energy consumption is modelled and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, for the authors Peng & Sun (2017), Kellens et al (2017a), Ingarao et al (2018) and Pour et al (2016), the central point of the discussions presented in the articles was the environmental dimensions of the additive manufacturing process. Peng & Sun (2017) performed a life cycle assessment of products for additive manufacturing, nevertheless, the effects of the energy consumption of the transportation stage were not mentioned. According to Pour et al (2016), even though the shorter supply chain reduces the need for transportation, due to the possibility of bringing production centers closer to customers, this factor is barely held in AM studies and no conclusion could be extracted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, for the authors Peng & Sun (2017), Kellens et al (2017a), Ingarao et al (2018) and Pour et al (2016), the central point of the discussions presented in the articles was the environmental dimensions of the additive manufacturing process. Peng & Sun (2017) performed a life cycle assessment of products for additive manufacturing, nevertheless, the effects of the energy consumption of the transportation stage were not mentioned. According to Pour et al (2016), even though the shorter supply chain reduces the need for transportation, due to the possibility of bringing production centers closer to customers, this factor is barely held in AM studies and no conclusion could be extracted.…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, the 51 studies analyzed were produced by the authors (Abdulhameed et al, 2019;Afshari et al, 2019;Agrawal & Vinodh, 2019;Ahmad & Enemuoh, 2020;Arrizubieta et al, 2020;Attaran, 2017;Böckin & Tillman, 2019;Campitelli et al, 2019;Caviggioli & Ughetto, 2019;Cerdas et al, 2017;Chen et al, 2015;Barros & Zwolinski, 2016;Esmaeilian et al, 2016;Faludi et al, 2019;Ford & Despeisse, 2016;Fruggiero et al, 2019;Garg & Lam, 2015;Ingarao et al, 2018;Kek et al, 2016;Kellens et al, 2017a, b;Kohtala, 2015;Kothman & Faber, 2016;Kunovjanek & Reiner, 2020;Li et al, 2017;Liu & De Giovanni, 2019;Ma et al, 2018;Maciel et al, 2019;Mele et al, 2020;Minetola & Eyers, 2018;Mrazović et al, 2018;Nagarajan & Haapala, 2018;Niaki et al, 2019;Nyamekye et al, 2015;Nyman & Sarlin, 2014;Paris et al, 2016;Peng et al, 2018;Peng & Sun, 2017;Pour et al, 2016;Priarone & Ingarao, 2017;Priarone et al, 2018;Saade et al, 2020;…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…It was reported that smart tools such as topology optimization provides optimal geometries and increased cost has no bearing on cost of finished parts. Peng and Sun [13] developed an analytical model for quantification of energy consumption in fused deposition of thermoplastics. Notable contribution on energy modelling in subtractive systems was made by Gutowski et al [14] by introducing a novel mathematical model for energy requirement in milling.…”
Section: Energy Modelling In Additive-subtractive Manufacturingmentioning
confidence: 99%
“…Fractions of the total time such as T lp1 , T ls1 for single part production can be calculated using Eqs. (12) and (13).…”
Section: Conventional Machiningmentioning
confidence: 99%
See 1 more Smart Citation